WATER DEFICIT AND SALINITY STRESS INDUCED ALTERATIONS IN MEMBRANE STABILITY INDEX, BIOMASS PRODUCTIVITY AND RELATIVE WATER CONTENT OF OENOTHERA BIENNIS L. GROWN IN WESTERN HIMALAYAN REGION - Sharma, Sikha (International Journal of Research -GRANTHAALAYAH, 2025)
In both natural and agricultural conditions plants are frequently exposed to environmental stresses. The productivity of plants is greatly affected by various environmental stresses that cause delayed germination, high seedling mortality, stunted growth, poor crop stand and lower yields. The O. biennis L,a medicinal plant was subjected to abiotic stresses, namely water deficit (-0.01 M Pa, -0.03 M Pa, -0.05 M Pa, -0.07 M Pa) and NaCl (25 mM, 50 mM, 75 mM and 100 mM) for long term . So, the present study aimed at determining the impact of water and salinity stress on plant fresh and dry weight, relative water content and membrane stability index after an interval of 30 days i,e. 30, 60, 90,120, 150,180 and 210 days after the induction of water and salinity stress. Increase in fresh weight and dry weight were noticed during the vegetative stage, earlier flowering stage after that biomass productivity decreased both in untreated and treated plants. It is evident from the results that with an increase in the intensity of stress a progressive decrease in the relative water content of leaves and membrane stability Index were noticed under both stress conditions and maximum decrease was noticed at 100 mM NaCl.So,these findings render Oenothera a sensitive plant at higher stress condions. However, changes in characteristics were realistic upto moderate stresses concentrations